2016
DOI: 10.1080/23723556.2016.1225546
|View full text |Cite
|
Sign up to set email alerts
|

Suv39h1 links the SUMO pathway to constitutive heterochromatin

Abstract: The Suv39h lysine methyltransferases, known as key enzymes responsible for histone H3 lysine 9 methylation, are critical for heterochromatin protein 1 enrichment at constitutive heterochromatin. Our recent findings reveal a new role for the Suv39h1 paralog that links it to SUMO pathway function at constitutive heterochromatin. KEYWORDSHeterochromatin; HP1; nuclear organization; SUMO pathway; suv39h1Heterochromatin has long been considered an inert part of the genome, merely gathering repetitive sequences. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The observations that modified ERα was detected as early as 20 min, i.e., before the peak of binding to DNA, and was found in both the chromatin-bound and the nuclear matrix fractions in MCF-7 cells at 1 h [24], are compatible with SUMOylated ERα being associated to DNA. SUMOylation of several general TFs or enhancer factors, including nuclear receptors, was previously reported to take place on DNA [49, 50] and to be associated with transcriptional repression [45, 46, 48, 5155]. Accordingly, SUMO2/3 ChIP-Seq peaks were enriched in different transcription factor-binding sites, especially CTCF motifs.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that modified ERα was detected as early as 20 min, i.e., before the peak of binding to DNA, and was found in both the chromatin-bound and the nuclear matrix fractions in MCF-7 cells at 1 h [24], are compatible with SUMOylated ERα being associated to DNA. SUMOylation of several general TFs or enhancer factors, including nuclear receptors, was previously reported to take place on DNA [49, 50] and to be associated with transcriptional repression [45, 46, 48, 5155]. Accordingly, SUMO2/3 ChIP-Seq peaks were enriched in different transcription factor-binding sites, especially CTCF motifs.…”
Section: Discussionmentioning
confidence: 99%
“…SUMOylation is also implicated in several aspects of heterochromatin formation in different genomic contexts in mammals. Studies in murine cell lines have shown that SUMOylation of HP1α regulates its de novo localization to pericentric chromatin, with Suv39h1 acting as a SUMO E3 ligase (Maison et al, 2011(Maison et al, , 2016. SUMOylation of the core histone H4 induces HP1γ recruitment and local silencing in human cell lines (Shiio and Eisenman, 2003).…”
Section: The Role Of Sumo In Recruiting the Silencing Complexmentioning
confidence: 99%
“…Several studies have shown the implication of SUMO proteins in transcription repression regulation and maintenance of silenced heterochromatin [63]. HP1α can be SUMOylated at the hinge domain by SUMO1, which is crucial for its targeting to pericentric heterochromatin in mice [45]; the methyltransferase Su(var)39H1, but not Su(var)39H2, seems to enhance this SUMOylation [64]. Following HP1α deposition at the pericentric heterochromatin, HP1α SUMOylation is rapidly reversed by SENP7, necessary to stabilize and maintain its binding to chromatin [65].…”
Section: Sumoylationmentioning
confidence: 99%